2023
DOI: 10.1021/acs.iecr.2c03007
|View full text |Cite
|
Sign up to set email alerts
|

La-Doped Alumina, Lanthanum Aluminate, Lanthanum Hexaaluminate, and Related Compounds: A Review Covering Synthesis, Structure, and Practical Importance

Abstract: Advanced materials based on lanthanum–aluminum oxides are useful for many practical applications, not the least in catalysis, energy conversion and energy storage systems designed for a sustainable world economy. The three main La–Al–O (LAO) combinations of commercial interest are La-doped aluminas (LDA), lanthanum monoaluminate (LMA, a perovskite), and lanthanum hexaaluminate (LHA). Usually, the literature treats doped aluminas, perovskites, and hexaaluminates separately. The current review tries to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 504 publications
0
2
0
Order By: Relevance
“…The synthesis of LHA from a pellet by the wet impregnation method is simpler than the so-gel and coprecipitation methods [11]. Hence, the wet impregnation method was employed to develop LHA support.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The synthesis of LHA from a pellet by the wet impregnation method is simpler than the so-gel and coprecipitation methods [11]. Hence, the wet impregnation method was employed to develop LHA support.…”
Section: Resultsmentioning
confidence: 99%
“…The wet-impregnation method [11,21] was used to prepare a Pt-LHA catalyst (Figure 1). First, a 1/8 Al 2 O 3 pellet was crushed by using a blender to get different mesh sizes such as 12-14, 14-16, 16-20, 20-25, and 25-30, and it was separated by using the sieving method.…”
Section: Catalyst Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that they could maintain a high specic surface area of 20 m 2 g −1 even aer exposure at 1200 °C for 4 h. 123 As a result, these hexaaluminates are usually employed as carriers for active metals in catalyzing the decomposition and combustion of ADN. [124][125][126][127] Jo et al 128 loaded Pt on Sr 0.8 La 0.2 -MnAl 11 O 19 by the immersion method followed by calcination at 550 °C and 1200 °C to obtain Pt/hexaaluminate catalysts, respectively. According to the experimental results, the catalysts exhibited similar catalytic activity, and both could reduce the onset decomposition temperature of ADN-based monopropellant by 65 °C in a batch reactor.…”
Section: Selection Of Carriers For Adn-based Monopropellant Liquid Pr...mentioning
confidence: 99%
“…La 2 O 3 is known to stabilize Al 2 O 3 by either inhibiting a phase transition or by forming mixed oxides [44][45][46]. The high-temperature stability of 20La is most likely related to the ability to delay phase changes of metal oxide supports at high temperatures, which makes La a frequently used dopant for Al 2 O 3 [47][48][49]. This leads to a more stable catalytic system exhibiting a steadier performance without significant drops in activity and selectivity.…”
Section: Variation Of the Reo Dopantmentioning
confidence: 99%